Kodėl administraciniam procesui (ne)reikalinga kasacija? - Jokšas, Deividas; Katiševskaja, Erika (Vilnius University Open Series, 2021)
The article analyses the system of administrative courts, its advantages, disadvantages and possible improvements.
Keywords: none